Kontribusi Kecerdasan Emosional dan Kecerdasan Sosial terhadap Kinerja Pegawai pada Organisasi Perangkat Daerah Kabupaten Tanah Datar - Yeyen Oktaviani; Syamsir Syamsir (Journal of Education on Social Science (JESS), 2018)
This study aimed to determine the contribution of emotional intelligence and social intelligence on the performance of employees in the Local Apparatus Organization of Tanah Datar Regency. This study was motivated by various problems which indicated the low quality of employee performance which was allegedly related to the low emotional intelligence and social intelligence of the employees. This was a quantitative research whose population was all civil servants in the organization totaling 1.596 people. The sample in this study consisted of 320 respondents who were determined using the Slovin formula with an error rate of 5% and set through Multistage Random Sampling technique. Data in this study were collected trough questionnaires with Likert scale measurement and analyzed with multiple linear regression test. The results of this study showed that there was a contribution of emotional intelligence to employee performance by 41,3%. There was also a contribution of social intelligence to employee performance amounted to 48,3%. At the same time, the contribution of emotional and social intelligence on the performance of employees in the Local Apparatus Organization of Tanah Datar Regency were 53,2%. So it could be concluded that emotional intelligence and social intelligence contributed significantly to employee performances.